Perancangan Sistem Informasi Penjualan Koperasi di Kota Salatiga menggunakan Framework CodeIgneter - Evi Maria; Purwanto Purwanto; Teguh Wahyono (STMIK Budi Darma, 2022)
In the era of the industrial revolution 4.0, the management of cooperatives is still carried out conventionally, and a few cooperatives have used information technology to manage their business. As a result, cooperatives are late, and some need to report the financial performance of cooperatives, so the level of member trust in cooperatives drops, and many cooperatives are inactive. This research aims to design a sales information system for cooperatives in Salatiga City. The sales information system was chosen because 83.33 percent of cooperatives in Salatiga City are consumer and producer cooperatives whose activities serve goods sales transactions. This research focuses on designing systems starting from updating goods, sales transactions, payments, and financial reporting for goods sales transactions. This research provides solutions to the problems experienced by cooperatives in the City of Salatiga related to the length of time for recording and reporting finances. So many cooperatives do not report their financial performance to the Office of Cooperatives and Micro, Small, and Medium Enterprises and do not hold an Annual Member Meeting. The cooperative sales information system is developed on a web-based basis, using the waterfall development model, the CodeIgniter framework, and MySQL database. This research results in the creation of a website-based sales information system that has been tested and can be used for all consumer and producer cooperatives in Salatiga